THE ROLE OF CORPORATE GOVERNANCE MECHANISM, FINANCIAL DISTRESS, AND FIRM PERFORMANCE ON EARNINGS MANAGEMENT WITH AUDIT QUALITY AS A MODERATING VARIABLE - Boli, Hubertus Ade Resha Raditya; Ferdian, Rafdhi Ikram (SINERGI : Jurnal Riset Ilmiah, 2025)
This study analyzes the effects of corporate governance mechanisms, financial distress, and company performance on earnings management, with audit quality as a moderating variable. Earnings management is measured using the EM proxy, while corporate governance is assessed through institutional ownership (INSTOWN) and ownership concentration (OWNCON). Financial distress is represented by the debt-to-equity ratio (DER), company performance by Tobin’s Q, and audit quality by the presence of a Big Four auditor (BIG4). Using secondary data from 385 industrial sector companies across ASEAN-5, Australia, New Zealand, and South Korea, this study finds that INSTOWN positively affects earnings management, while OWCON, financial distress, and company performance have negative effects. However, audit quality does not moderate the relationships between institutional ownership, ownership concentration, financial distress, and company performance with earnings management. These findings highlight the need for strong corporate governance, prudent financial management, and high audit quality to mitigate earnings management risks and enhance stakeholder trust.